Carboxymethyl cellulose stabilized ZnO/biochar nanocomposites: Enhanced adsorption and inhibited photocatalytic degradation of methylene blue. (April 2018) - Wang, Shengsen; Zhou, Yanxia; Han, Shuwen; Wang, Nong; Yin, Weiqin; Yin, Xianqiang; Gao, Bin; Wang, Xiaozhi; Wang, Jun
Abstract: Biochar(BC)-supported nanoscaled zinc oxide (nZO) was encapsulated either with (nZORc/BC) or with no (nZOR/BC) sodium carboxymethyl cellulose (CMC). The X-ray diffraction and ultraviolet (UV)-visible-near infrared spectrophotometry revealed that nZO of 16, 10, and 20 nm with energy band gaps of 2.79, 3.68 and 2.62 eV were synthesized for nZOR/BC, nZORc/BC and nZO/BC, respectively. The Langmuir isotherm predicted saturated sorption of methylene blue (MB) was 17.01 g kg −1 for nZORc/BC, over 19 times greater than nZOR/BC and nZO/BC. Under UV irradiation, 10.9, 61.6, 83.1, and 41.6% of MB were degraded for nZORc/BC, nZO/BC, nZOR/BC and BC. The scavenging experiment revealed hydroxyl radical dominated CMC degradation. Exogenous CMC (2 g L −1 ) increased MB sorption from 10.6% to 73.1%, but decreased MB degradation from 80.7% to 41.1%, relative to nZOR/BC. Thus, CMC could increase MB sorption by electrostatic attraction and other possible mechanisms. The compromised MB degradation may be ascribed to reduced availability of hydroxyl and superoxide radicals to degrade MB, and increased band gap energy of ZnO. Highlights: CMC reduced ZnO crystallite size but increased band gap of ZnO/biochar composite. UV-irradiated ZnO and biochar generated ROS in MB degradation. CMC increases MB sorption by electrostatic attraction and other mechanisms. CMC can react with ROS and reduce ROS availability for MB degradation. CMC capping is not suitable for MB degradation by ZnO.